High‐Pressure and High‐Temperature Single‐Crystal Elasticity of Cr‐Pyrope: Implications for the Density and Seismic Velocity of Subcontinental Lithospheric Mantle - Jingui Xu; Dawei Fan; Bo Li; Sergey N. Tkachev; Vitali B. Prakapenka; Dongzhou Zhang; Guangzhong Yang; Yi Zhou; Wenge Zhou (Geochemistry, Geophysics, Geosystems)
Abstract Single‐crystal X‐ray diffraction and Brillouin spectroscopy experiments were performed on a natural Cr‐pyrope (Prp71.0Alm12.6Sps0.7Grs3.5Uvr12.2) at high pressure and high temperature up to 11.0 GPa and 800 K. Fitting the collected data to the third‐order finite strain equation yields bulk modulus (KS0), shear modulus (G0), their pressure ((∂KS/∂P)T and (∂G/∂P)T) and temperature ((∂KS/∂T)P and (∂G/∂T)P) derivatives, KS0 = 167.7(8) GPa, G0 = 91.5(5) GPa, (∂KS/∂P)T = 4.3(1), (∂G/∂P)T = 1.4(1), (∂KS/∂T)P = −0.0175(1) GPa/K and (∂G/∂T)P = −0.0073(1) GPa/K. Using the obtained results, we examined whether the elastic properties of the Cr‐pyrope can be accurately calculated from those of endmembers including pyrope, almandine, grossular, and uvarovite assuming a linear relationship between elastic properties and composition (end‐member model). The results indicate that the end‐member model provides a sufficient approximation for the elastic properties of Cr‐pyrope in calculating the density and velocity of the subcontinental lithospheric mantle (SCLM). We modeled the densities and velocities of three typical types of SCLM (Archon, Proton, and Tecton) in order to investigate how the variation of chemical composition influences the SCLM. We obtained that the compositional change from the Archon to the Tecton increases the density of the SCLM significantly, which can be an important prerequisite for SCLM delamination. However, the compositional variation only slightly changes the velocity of the SCLM and the change is within the uncertainty of the calculation. Moreover, in comparison to the velocity, ρ/VP and ρ/VS are much more sensitive to the compositional change of the SCLM.